PERANCANGAN SISTEM INFORMASI PELAYANAN JASA LAUNDRY BERBASIS ANDROID PADA LAUNDRY EXPRESS - Widyastuti, Reni; Fahri Lubis, Zidanne Zulkifli (Universitas PGRI Semarang, 2022)
Laundry Express is a business unit that provides washing and drying services for fabrics such as clothes, bed linen, curtains and others with the Jabotabek area of operation. This laundry service is provided to consumers in the form of washing services consisting of ironing and dry cleaning as well as laundry pick-up and drop-off services by couriers. Currently services at Laundry Express are carried out conventionally where all recording and reports are done manually so that problems occur such as shipping transaction records and laundry services that are lost or forgotten to be recorded so that Laundry Express consumers complain as a result of not optimal service and the difficulty of making a recap of the reports provided. for laundry owners. The author in this study designed a system that functions to overcome the problems of Laundry Express services by using an object-oriented approach where the waterfall is a system development method. System depiction with UML using the Java programming language and an android-based editor, namely Android Studio, which functions to build applications provided that users can use it with a minimum requirement of Android 5.0 lollipop version. This research is a solution for Laundry Express for better service by providing easy access to data, fast and accurate transactions and report generation